2018
DOI: 10.3390/ijerph15010170
|View full text |Cite
|
Sign up to set email alerts
|

Global Mortality Burden of Cirrhosis and Liver Cancer Attributable to Injection Drug Use, 1990–2016: An Age-Period-Cohort and Spatial Autocorrelation Analysis

Abstract: We analyzed the temporal and spatial variations in mortality burden of cirrhosis and liver cancer attributable to injection drug use (IDU) from 1990 to 2016. Mortality data of IDU-attributable cirrhosis and IDU-attributable liver cancer on the global and national scales from 1990 to 2016 were collected from the Global Burden of Disease (GBD) studies. Age-period-cohort (APC) model analysis was used to analyze the global mortality trends of target disease, and spatial autocorrelation analysis based on Geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…Period effect reflects the immediate impact of social factors on the incidence of diseases. 29 In this study, the period effect decreased after 2005 compared with 2000 to 2004, which may relate to one or more achievements in the field of public health in China. In 1989, China launched the “Chinese Dietary Guideline”, and launched the revision version in 1997, 2007, and 2016, separately.…”
Section: Discussionmentioning
confidence: 66%
“…Period effect reflects the immediate impact of social factors on the incidence of diseases. 29 In this study, the period effect decreased after 2005 compared with 2000 to 2004, which may relate to one or more achievements in the field of public health in China. In 1989, China launched the “Chinese Dietary Guideline”, and launched the revision version in 1997, 2007, and 2016, separately.…”
Section: Discussionmentioning
confidence: 66%
“…The cohort effect reflects changes in disease risk in a particular birth cohort. 33 In the present study, the birth cohort effect showed that both males and females born more recently had lower risks of UTI. This may be related to changes in lifestyles, more-sanitary conditions, and improvements in health habits.…”
supporting
confidence: 50%
“…32 The period effect reflects the immediate impact of social factors on the incidence of disease. 33 The present study found that the risk of UTI in both males and females decreased after 2005 compared with 2000 to 2004. The reduced risk of male UTI may be related to greater attention being paid to male reproductive health in China in recent years.…”
supporting
confidence: 45%
“…The main causes of liver fibrosis include chronic hepatitis C infection, abusing alcohol, and steatohepatitis . Advanced liver fibrosis can progress to cirrhosis over time, and cirrhosis may cause serious complications, such as hepatocellular carcinoma, liver failure, and portal hypertension . Cirrhosis is one of the leading causes of death in China and worldwide; thus, it is urgently needed for a better understanding of the molecular mechanism of the liver fibrosis progression.…”
Section: Introductionmentioning
confidence: 99%